Evaluation of humoral immune responses of experimental animals to the recombinant SARS-CoV-2 spike ectodomain with the ISCOM adjuvant - V. A. Evseenko; A. V. Zaykovskaya; A. S. Gudymo; O. S. Taranov; S. E. Olkin; A. R. Imatdinov; E. Yu. Prudnikova; N. V. Danilchenko; I. S. Shulgina; M. N. Kosenko; E. I. Danilenko; S. A. Pyankov; et al. (Биопрепараты: Профилактика, диагностика, лечение, 2023)
Scientific relevance. The use of recombinant antigens in vaccine production is limited because vaccines based on such antigens tend to have low immunogenicity. However, a COVID-19 vaccine that combines recombinant SARS-CoV-2 spike glycoprotein as its antigen and virus-like immune-stimulating complexes (ISCOMs) as its adjuvant (Nuvaxovid) induces a protective virus-neutralising response. The State Research Center of Virology and Biotechnology “Vector” (hereinafter, Vector) has developed the ISCOM adjuvant Matrix-V, which plays a key role in inducing virus-neutralising antibodies. Studying Matrix-V will provide for the wide use of recombinant antigens combined with this adjuvant in the development and production of novel Russian vaccines.Aim. This study aimed to evaluate the humoral immune responses of experimental animals to intramuscular injections of a complex combining the recombinant Wuhan-type SARS-CoV-2 spike RBD antigen and the virus-like ISCOM adjuvant containing Quillaja saponaria saponins.Materials and methods. The Matrix-V ISCOM adjuvant was produced using Vector’s proprietary technology, which involves cross-flow filtration through Sartorius VivaFlow cassettes. To determine the saponin and residual detergent concentrations in Matrix-V, the authors conducted high-performance liquid chromatography. Having produced the recombinant SARS-CoV-2 RBD antigen, the authors used electron microscopy to analyse the ultrastructure of the ISCOM–antigen complex. In the study of the ISCOM–antigen complex, 25 female Balb/c mice (5 groups) and 15 male and female outbred guinea pigs (3 groups) received two intramuscular injections with a 14-day interval. Serum tests relied on virus neutralisation (VN) and enzyme-linked immunosorbent assay (ELISA) methods and used antigens of 8 SARS-CoV-2 variants (State Collection of Viruses and Rickettsia, Vector). The authors used Statistica 10 to analyse the results.Results. Two injections of the SARS-CoV-2 RBD antigen (mice: 7 μg, guinea pigs: 1 μg) alone did not induce statistically significant virus-neutralising antibody responses, as shown by the VN results. Two injections of the SARS-CoV-2 RBD antigen (mice: 7 μg, guinea pigs: 1 μg) adjuvanted with Matrix-V (25 μg) resulted in geometric mean antibody titres of 1:83–1:178 (mice) and 1:174–1:587 (guinea pigs) in the VN tests with the Wuhan variant. One injection of the antigen (1 μg or 7 μg) with Matrix-V (25 μg) induced antibodies only in individual cases, as demonstrated by the VN and/or ELISA results. The most intensive immune response was observed in ELISA tests with the Delta variant after two injections of the Ecto-S-Wuhan (1 μg) and Matrix-V (25 μg) complex. Immune responses did not differ between the group that received two injections of the Ecto-S-Wuhan antigen (1 μg) without the ISCOM adjuvant and the negative control group (titres below 1:100; p=0.95). Two injections of the SARS-CoV-2 RBD antigen (7 μg) without the ISCOM adjuvant induced antibodies in mice (titres between 1:248 and 1:1477).Conclusions. Two intramuscular injections of the complex containing the recombinant SARS-CoV-2 RBD antigen and the Matrix-V ISCOM adjuvant induce virus-neutralising antibodies. The approach proposed by the authors has the potential for use in the development of immunobiological medicinal products to prevent and treat a wide range of infectious diseases.